Analisis Pemanfaatan Media Sosial sebagai Strategi Pemasaran Brand Exsport - Ardhelia Fauzia; Wadiah Saadah; Erwin Permana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the effectiveness of utilizing social media as a digital marketing strategy for the Exsport brand in building brand awareness, increasing consumer engagement, and strengthening customer loyalty. The research methodology uses a descriptive qualitative approach with secondary data analysis of Exsport's social media content on Instagram, TikTok, and YouTube, as well as literature studies related to digital marketing strategies in the fashion industry. The results show that Exsport successfully communicates brand values ​​oriented towards a young, creative, and productive lifestyle through a consistent visual content strategy, collaboration with influencers, and participatory campaigns based on user-generated content and storytelling. This strategy has been proven to increase engagement rates, build emotional connections with consumers, and strengthen the brand's positive image amidst global competition. However, the effectiveness of Exsport's digital strategy requires sustainable, innovative, and adaptive content management to rapidly changing social media trends. Based on these findings, it is recommended that Exsport continue to innovate in content development, strengthen brand identity through creative narratives, and integrate digital strategies with offline marketing activities to create a more holistic customer experience. With this approach, social media serves not only as a promotional tool but also as a strategic instrument for expanding market reach, increasing competitiveness, and maintaining customer loyalty in the Indonesian fashion industry.